Developing of Discon E-Module Based on Android in Force and Motion Material - Rahayu, Enny; Azizah, Azizah; Isman, Muhammad; Sari Sitepu, Melyani; Idayanti, Sukmah (Universitas Pancasakti Tegal, 2023)
The problem in this study is that the Learning media is quite limited and less interesting. The difficulty of teachers controlling the online learning process during the pandemic. The purpose of this research is to develop a science practicum e-module with a valid and practical Android-based discovery learning approach. This research is research and development with the Borg and Gall model. The 5 stages of this research are preliminary research and analysis, developing initial products, expert validation and revision, small-scale field trials and product revisions, and large-scale field trials. The research instrument used interviews and media validation questionnaire sheets, material validation , and user validation. This study was conducted on a small scale where the subjects were class teachers and 6 students of Grade IV SD Muhammadiyah 1 Palu. Based on the results of data analysis obtained material validity values of 23, 12, 9, 11, and 12 with a very strong Category. user (student) satisfaction respectively 91.7, 88.3, ​​96.7, and 86.7 7, and user (teacher) satisfaction of 90, 70, 100, and 100 with very good category. So it can be concluded that the Android-based E-module discon (E-module DISROID) developed in the criteria is very valid and practical. So that this module can be used in science learning, especially for practicum activities in Grade IV of elementary school.